Resistance of wooden lacquered surface to scratching - Temelkova, Anastasija; Jevtic, Petronije (Ss. Cyril and Methodius University, Skopje, North Macedonia, Faculty of Design and Technologies of Furniture and Interior, Skopje, 2019)
In this study the resistance of lacquered wood surfaces to scratching was analyzed. The samples for varnishing were previously prepared by second level and third level of grinding. Further, the samples were surface treated with unadventurous 2K polyurethane coating and modified 2K alkyd urethane coating. The aim of this study is to determine which of the used coatings will give a better resistance to scratching. The test results indicate that surfaces treated with modified 2K alkyd urethane coating give greater resistance to scratching compared to the surfaces treated with unadventurous 2K polyurethane coating
Keywords: surface, resistance, scratching, grinding, 2K polyurethane coating, 2K alkyd urethane coating